The teaching of English reading in lower primary grades : an eval uation of Busia Municipal Council - Shiundu, Margaret (Kampala, 2013)
Unpublished dissertation (MLLED) - Makerere University, 2013.
Includes bibliographical references.
Keywords: English language -- Study and teaching (Elementary) -- Uganda -- Bus ia Municipal Council; Children -- Language -- Study and teaching -- Uganda -- BUsia Munici pal Council; Multicultural education